LACANIAN PSYCHOANALYTICAL ANALYSIS OF ADELE’S SONG EASY ON ME - Lisma Ayu Arditha; Na’ilah Farashifah; Luke Zefranezra Mulyanto; Anggoro Cahyo Wicaksono; Kusuma Wijaya; Rommel Utungga Pasopati (Seminar Nasional Hasil Riset dan Pengabdian, 2025)
This study aims to analyze Adele's song Easy on Me through Jacques Lacan's psychoanalytic approach using descriptive qualitative methods. The research data consists of song lyrics which are then interpreted using Lacan's main concepts, namely the Real, the Imaginary, and the Symbolic. The analysis shows that the lyrics represent the inner conflict of the lyrical character in facing separation and an unresolved past. The request to “go easy on me” reflects the need for recognition in the Imaginary realm, as well as the guilt and responsibility present in the Symbolic. Meanwhile, emotional experiences that cannot be fully expressed through language describe the presence of the Real as something traumatic and unattainable. The results of this study show that song lyrics are not only emotional expressions, but also spaces of unconscious representation that can be understood through Lacan's psychoanalytic framework. In conclusion, this study points out that Adele’s song matches with Lacanian perspectives on psychoanalysis that mediates trauma through language of everyday life.